Redefining Arabic Poetry: Descriptive Historical Perspective - Siti Amsariah; Fathalla Mohammed Fathalla Zekaizak (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2024)
Poetry has captivated people from ancient times to the modern era, sparking numerous debates, conflicts, and rivalries. This phenomenon has led to the creation of many books, anthologies, newspapers, and magazines. Countless debates have ensued, news and stories have proliferated, and numerous studies have been conducted on this subject from various perspectives and with different objectives. This research examines poetry from the standpoint of its intrinsic values. The article investigates and analyzes the wisdom of studying poetry, its virtues, and its diverse benefits. The aim of this study is to explore the implications of studying and reading poetry, as well as its merits and advantages. The method used is descriptive-historical, based on the selection of relevant events and facts, and the collection of data pertinent to the research objectives. This article begins with an introduction followed by three main sections: first, the virtues of poetry and the wisdom of studying it; second, the benefits of poetry; and third, the appreciation and rewards for poets and their work. The research findings lead to several significant conclusions: high-quality poetry possesses many virtues and benefits, both in terms of human relationships with the divine and with fellow human beings. These include the promise of paradise and receiving prayers and praise from Allah's beloved, Prophet Muhammad SAW. Poetry serves as a means of expressing gratitude to Allah, enhancing understanding of the Quran, and appreciating its eloquence. It brings joy and longing to the hearts of Muslims, inspires courage in the brave, elevates the spirit, comforts the soul, and bolsters moral fortitude. Such aspects of poetry contribute to spiritual well-being, foster acceptance and openness in social life, and serve as a source of great reward and appreciation.